Diversity and Structure of Aquatic Insect Communities in Relation to Water Quality Parameters in the Kasetsart University Drainage Ditches, Central Thailand - Prommi, Taeng On; Khamboonruang , Pattrawan; Klorvuttimontara, Sravut (Journal of Food Health and Bioenvironmental Science, 2024)
This study evaluates the impact of anthropogenic influence on the drainage ditches of Kasetsart University's Kamphaeng Saen Campus in Nakhon Pathom Province, using water quality measurements and aquatic insect data collected during a six-month period from October 2022 to March 2023. Six sampling ditches with various human activities were chosen. Organic wastes from agriculture, residences and buildings were the primary causes of pollution. A total of 6,232 aquatic insects from six orders—Hemiptera (28.32%), Coleoptera (7.76%), Odonata (12.52%), Diptera (36.33%), Ephemeroptera (2.47%) and Trichoptera (12.6%)—were collected. In the current study, the order Diptera was the most diversified and relatively abundant in all sampling sites. However, the order Trichoptera was most common in KUKPS6, a running water ditch. The orders Hemiptera and Coleoptera had the highest abundance in the KUKPS1, while Odonata and Ephemeroptera had the highest abundance in KUKPS2. The Shannon-Weiner diversity index for aquatic insects was between 1.527 and 2.959, indicating slightly good water quality. According to the Canonical Correspondence Analysis (CCA), dissolved oxygen, orthophosphate, nitrate-nitrogen, turbidity and pH were the most influential factors. Based on the data on physicochemical water quality and entomofauna composition, the results concluded that Kasetsart University's drainage ditches were slightly polluted.